Perspektif Moral Knowing Thomas Lickona Pada Pembentukan Karakter Disiplin Siswa Di Sekolah Dasar - Darwanti, Asri; Fauziati, Endang; Fathoni, Achmad; Minsih, Minsih (Cetta: Jurnal Ilmu Pendidikan, 2025)
The development of student character has become a primary concern in the field of education, particularly in instilling the values of discipline from an early age. One relevant approach in this effort is the Moral Knowing approach, which emphasizes the importance of moral understanding and knowledge in shaping behavior. This study aims to describe the implementation of the Moral Knowing approach in shaping students' discipline character at SDN 02 Ngadiluwih. This approach is believed to foster students' moral awareness as a foundation for acting in accordance with prevailing values. This study employs a descriptive qualitative method. Data were collected through observation, interviews with teachers and students, and documentation of school activities. The research subjects consisted of classroom teachers, students, and the principal. Data were analyzed through the processes of data reduction, data display, and conclusion drawing. The findings indicate that the Moral Knowing approach is implemented through various strategies, such as habituation of morning and afternoon routines, teacher role modeling, use of visual media like character value posters, and student involvement in extracurricular activities that emphasize discipline, such as Scouts. Through these activities, students not only learn the meaning of discipline but also understand the moral reasons behind it and demonstrate more orderly behavior in both academic and social activities. The conclusion of this study is that the Moral Knowing approach is effective in shaping students’ discipline character through the enhancement of moral awareness, the reinforcement of values, and consistent habituation within the school environment.